The Use of Antimicrobials in Italian Heavy Pig Fattening Farms - Federico Scali; Giovanni Santucci; Antonio M. Maisano; Francesca Giudici; Federica Guadagno; Matteo Tonni; Alberto Amicabile; Nicoletta Formenti; Enrico Giacomini; Massimiliano Lazzaro; Giorgio Bontempi; Nicoletta Vitale; et al. (MDPI AG, 2020)
Data on antimicrobial use (AMU) in heavy pig production (>150 kg) are limited. The aim of this study was to investigate the AMU in this production. Data from 2015 were collected for 143 fattening farms. The AMU was estimated through a treatment index per 100 days (TI100) using the defined daily dose animal for Italy (DDDAit). When possible, a comparison with the European Medicines Agency's defined daily doses for animals (DDDvet) was performed. The median TI100 was 10.7 (range, 0.2-49.5). Group treatments represented 94.6% of overall consumption. The AMU calculated using DDDAit and DDDvet were strongly correlated (ρ = 0.976; p < 0.001). The AMU was negatively correlated with injectables use (ρ = −0.46, p < 0.001) and positively correlated with oral products (ρ = 0.21, p = 0.014), premixes (ρ = 0.26, p = 0.002), and mortality (ρ = 0.18; p = 0.027). Farm size was negatively correlated with AMU (ρ = −0.29, p < 0.001). Smaller farms were more frequently above the median TI100 (odds ratio = 2.3, 95% confidence interval = 1.2-4.7), suggesting that they may have lower biosecurity and management standards. The results of this study should provide useful insights for the development of an Italian monitoring system.